2021
DOI: 10.1101/2021.01.21.20248810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduction of brooding and more general depressive symptoms after fMRI neurofeedback targeting a melancholic functional-connectivity biomarker

Abstract: Depressive disorders contribute heavily to global disease burden; This is possibly because patients are usually treated homogeneously, despite having heterogeneous symptoms with differing underlying neural mechanisms. On the contrary, treatment that directly influences the neural circuit relevant to an individual patient’s subset of symptoms might more precisely and thus effectively aid in the alleviation of their specific symptoms. We tested this hypothesis, using fMRI functional connectivity neurofeedback to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…The 16 FCs discovered in this study are promising candidates as theranostic biomarkers for depression symptoms. Future work should investigate whether modulation of FCs could be an effective treatment for depression symptoms by using an intervention method with regard to FCs, such as functional connectivity neurofeedback training (53)(54)(55)(56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…The 16 FCs discovered in this study are promising candidates as theranostic biomarkers for depression symptoms. Future work should investigate whether modulation of FCs could be an effective treatment for depression symptoms by using an intervention method with regard to FCs, such as functional connectivity neurofeedback training (53)(54)(55)(56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…Brooding factor is specifically thought to be associated with depression and mistake concern (Treynor et al, 2003;Hasegawa 2013), which is considered a specific trait of melancholic depression. The EEG network feature estimated from SPLICE was not directly calculated from the target FC like FCNef (Yamada et al, 2017;Taylor et al, 2021). However, we confirmed the statistical equivalence between EEG network features and fMRI data in the selection process of SPLICE module.…”
Section: Improvement Of Depressive Symptoms Due To Eeg Nf Trainingmentioning
confidence: 62%
“…It is The copyright holder for this preprint this version posted June 21, 2021. ; https://doi.org/10.1101/2021.06.20.449196 doi: bioRxiv preprint then found large effect size on RRS (total, brooding and reflection) compared the NF group with the sham group, but not on BDI. The FCNef protocol of Taylor et al (2021) for four days' training with fMRI showed significant reduction of BDI and brooding in RRS.…”
Section: Improvement Of Depressive Symptoms Due To Eeg Nf Trainingmentioning
confidence: 91%
See 2 more Smart Citations